Risk management concepts and guidance - Pritchard, Carl L. (Gildan, 2019)
This new edition of Risk Management: Concepts and Guidance supplies a look at risk in light of current information, yet remains grounded in the history of risk practice. Taking a holistic approach, it examines risk as a blend of environmental, programmatic, and situational concerns.